Membangun Desa Melalui Kuliah Kerja Nyata “Penyuluhan Pentingnya Pendidikan” - Muhammad Tharmizi Junaid; Aan Digita Malik; Dodi Apriadi; Nizhamuddin AB; Rusdy Setiawan (CV. Multi Kreasi Media, 2023)
− Education is a need that must be fulfilled in the life of society, nation and water. Through education, both formal and non-formal, students will experience a process of change in themselves both in knowledge and in behavior. This process of self-change is called learning. Learning motivation is one of the factors that also determines effectiveness in learning. A learner will learn well if there is a driving factor, namely learning motivation. Counseling activities related to the importance of Education were carried out by UBT KKN Students and also Field Assistant Lecturers. The activity was carried out in Semunad Village, Tulin Onsoi sub-district, Nunukan Regency, North Kalimantan Province. This activity was welcomed by the figures in the village, starting from the customary leader, RT head, and community leaders. With the completion of the activity, it is hoped that it will increase the motivation of the children to be able to pursue education to the highest possible level